Impact of age on the cerebrospinal fluid spaces: high-convexity and medial subarachnoid spaces decrease with age - Yosuke Hidaka; Mamoru Hashimoto; Takashi Suehiro; Ryuji Fukuhara; Tomohisa Ishikawa; Naoko Tsunoda; Asuka Koyama; Kazuki Honda; Yusuke Miyagawa; Kazuhiro Yoshiura; Shuken Boku; Kazunari Ishii; et al. (Fluids and Barriers of the CNS, 2022)
Abstract Background Impaired cerebrospinal fluid (CSF) dynamics may contribute to the pathophysiology of neurodegenerative diseases, and play a crucial role in brain health in older people; nonetheless, such age-related changes have not been well elucidated. Disproportionately enlarged subarachnoid-space hydrocephalus (DESH) is a neuroimaging phenotype of idiopathic normal-pressure hydrocephalus, originating from impaired CSF dynamics, and closely associated with aging. This study aimed to investigate the pathophysiology of DESH and determine age-related changes in CSF dynamics. Methods Using magnetic resonance imaging, we investigated the pathophysiology of DESH by quantitatively evaluating the volumes of DESH-related regions (ventricles [VS], Sylvian fissure [SF], and subarachnoid spaces at high convexity and midline [SHM]) and brain parenchyma in community-dwelling individuals aged  ≥ 65 years. DESH-related regions were assessed using a visual rating scale, and volumes measured using voxel-based morphometry. Brain parenchyma volumes were measured using FreeSurfer software. Results Data from 1,356 individuals were analyzed, and 25 (1.8%) individuals had DESH. Regarding the relationships between the volume of each CSF space and age, VS and SF volumes increased with age, whereas SHM volume did not increase. VS and SF volumes increased as the whole brain volume decreased, whereas SHM volume did not increase even if the whole brain volume decreased; that is, SHM did not expand even if brain atrophy progressed. Moreover, lower Mini-Mental State Examination scores were significantly associated with lower SHM volume and higher VS volume. These associations remained significant even when individuals with DESH were excluded. Conclusions This study showed that the volume of high-convexity and medial subarachnoid spaces did not expand and tended to decrease with age; the human brain continuously progresses toward a “DESH-like” morphology with aging in community-dwelling older persons (i.e., DESH might be an “accelerated aging stage” rather than an “age-related disorder”). Our results indicated that brain atrophy may be associated with the development of “DESH-like” morphology. In addition, this morphological change, as well as brain atrophy, is an important condition associated with cognitive decline in older adults. Our findings highlight the importance of investigating the aging process of CSF dynamics in the human brain to preserve brain health in older people.